SOL GEL PROCESS FOR THE PREPARATION OF SOLID ELECTROLYTE MATERIAL - Durrani, S. K.; Akhtar, J.; Qureshi, A. H.; Qazi, N. K. (The Nucleus, 2020)
The reality that fossil fuels are running out is driving the development of fuel cells. These fuel cells offer attractive and alternative energy sources because of high conversion efficiency, low pollution, light weight, and high power density. In this article, status of fuel cells and ceramic fuel cells have been discussed with particular emphasis on stabilized zirconia widely used as solid electrolyte material in solid oxide fuel cells (SOFCs) due to its high oxygen ion conductivity. The study is also focused on low cost process for synthesis of 12mol% yttria stabilized zirconia (12YSZ) powder from the zirconia sol prepared by hydrothermal treatment of zirconium nitrate solution with an aqueous electrolyte extraction by organic extractant. The 12YSZ powder found to be pure white crystalline. 12YSZ calcined powder were sintered at 1200ÂºC for 1-6 hours durations. Phase, purity, crystallinity and morphology of 12YSZ were examined by differential thermal analysis (DTA), thermogravimetry (TG), scanning electron microscopy (SEM) and X-ray diffraction (XRD) techniques. SEM indicated the size range 0.2 - 5 micron. The results revealed that the product material (pellet) can be sintered into uniformly size fine grained ceramic of > 98% theoretical density around 1200oC for 6 hours as compared to the pellet sintered for 1 hour at the same temperature.